Basic Education in the Era of Society 5.0: Opportunities and Challenges - Heri Dermawan; Sri Sumarni (International Journal of Educatio Elementaria and Psychologia, 2024)
In the context of technology integration in basic education in the Society 5.0 era, this research aims to explore the challenges, opportunities and impact on the curriculum, the role of teachers and the learning process. Through a qualitative literature study approach, we analyzed academic literature to understand how technology can influence curriculum development that is responsive to 21st century skills, the changing role of teachers as facilitators of digital learning, and the implementation of technology in interactive learning such as e-learning and game-based learning . The findings highlight the need for developing digital skills for teachers, as well as challenges related to technology accessibility and the digital divide among students. In conclusion, the integration of technology in basic education offers significant opportunities to improve the quality of learning, but requires cross-sector collaboration to ensure that all students can access technology equally to achieve inclusive and relevant education.